Prevalence of Seasonal Variation of Haemorrhagic stroke more in winter than summer and its common risk factors (Community Based Medical Journal, 2016)
The present descriptive cross-sectional study was conducted in the department of medicine, Community Based Medical College Hospital Bangladesh over a period of one year during March 2013 to February 2014. The study was conducted to describe Haemorrhagic stroke during summer and winter. An attempt was also made to observe in the frequency of common risk factors of stroke by seasons. A total 146 patients of any age irrespective of sex fulfilling the WHO criteria of acute stroke and confirmed by CT Scan were selected from consecutive admission in the Department of Medicine, Community Based Medical College Hospital Bangladesh. Detail history and through clinical examinations were done. Routine and relevant investigations were carried out. The mean age of the patients was 60.9±14.3 years. A male preponderance was observed in the study. In summer 65.8% of patients and in winter 34.2% patients were presented. Ischemic stroke was present in 52.1% patients and 47.9% patients had haemorrhagic stoke. The study found that the frequency of ischemic stroke during summer (65.8%) was significantly greater than that during winter (34.2%). The frequency of haemorrhagic stroke during winter (65.8%) significant greater than that during summer (39.6%). Hypertension was the most important risk factor and other risk factors were smoking. Diabetes mellitus, tobacco chewing, ischamic heart disease, dyslipidaemia, oral contraceptive pill, alcohol consumption atrial fibrillation and past history of stroke. Increasing age was also noted as a risk factor (60.7%>60 years). Most of the risk factors were homogenously distributed between two seasons and between ischemic and haemorrhagic group. Hypertension was significantly higher in haemorrhagic stroke patients compared to ischemic stroke patients.CBMJ 2016 January: Vol. 05 No. 01 P: 09-13